Violence-Related Traumatic Brain Injury in Justice-Involved Women. (October 2018) - Wall, Kristi; Gorgens, Kim; Dettmer, Judy; Davis, Terri M.; Gafford, Jennifer
The present study investigated gender differences in the prevalence and incidence of violence-related traumatic brain injury (TBI) among justice-involved individuals, as well as potential associations between violence-related TBI and select biopsychosocial variables among women in the sample. Data from 409 justice-involved individuals were analyzed, and men and women were compared for rate of violence-related TBI. Women were grouped by violence-related TBI history and compared on eight biopsychosocial variables. Gender was significantly associated with multiple TBIs and multiple violence-related TBIs. History of violence-related TBI in women was associated with physical health problems and incarceration history. This research revealed a high rate of violence-related multiple TBIs among justice-involved women. Violence-related TBIs were associated with more prevalent physical illness and increased incarceration times. Identification of justice-involved women with these injuries may help clinicians better tailor services to improve inmate outcomes and reduce cost burdens to justice systems.